THE PORTRAYAL OF PATRIARCHAL OPPRESSION TOWARDS DEJAH THORIS IN THE JOHN CARTER MOVIE BY ANDREW STANTON - Rudiansyah, Rudiansyah; Surya, Satyawati; Fatimah, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
Gender inequality between men and women are still having the same core problematic in the real life. This research is aimed to answer the questions about the portrayal of the patriarchal system in the John Carter movie and the influence of patriarchal system towards Dejah Thoris’ life in that movie. This research used two theories, namely Johnson’s Patriarchal theory and Young’s Oppression theory. The method that had been used by the researcher was the qualitative method. The result of this research shows that there are four kinds of patriarchal system. First, men dominate in politic sphere, military and domestic field. Second, men are identified as the leaders who have the ability to control and dominate women. Third, men regularly are involved in any situation and they always become the center of attention in society. Lastly, men character in the movie shows their obsession with control, it proved by their passion to controlling over in wide scale both in private and public sphere. Then, the fact about how Dejah Thoris is the victim of the oppressor that makes her life exploited, marginalized, less of power, forced by cultural imperialism, and treated violently. Despite, she resists to be silent and accept her path as an inferior person, however, she still be taken out and neglected.